The actor in you twelve simple steps to understanding the art of acting - Benedetti, Robert L. (Upper Saddle River, New Jersey Pearson Education, Inc., 2015)
The Actor in You presents a thorough and systematic exposure to the fundamentals of the acting process in simple, direct language and a streamlined structure. This title draws on exercises and examples from students' everyday lives, well-known plays, and popular television programs to lead the beginning student through the process of creating a role.
Understanding the actor's job -- Relaxing and centering -- Your voice and speech -- Working together -- Exploring the text -- Objectives and actions -- Beats, scenes, superobjective, and spine -- The foundations of character -- Personalization -- Early rehearsals -- Staging and final rehearsals -- The performance and after.
Includes bibliographical references and index.
Keywords: Acting